APPLICATION OF DIGITAL TWIN TECHNOLOGY IN APPAREL DESIGN, VIRTUAL TESTING, AND PRODUCTION PLANNING (Web of Technology: Multidimensional Research Journal, 2026)
The rapid advancement of Industry 4.0 technologies has significantly transformed manufacturing systems, including the apparel industry. Digital twin technology has emerged as an innovative tool for integrating virtual and physical production environments. This study investigates the development of a digital twin of a garment product for design, virtual testing, and technological preparation of production. The proposed framework combines three-dimensional garment modeling, anthropometric data processing, material simulation, and manufacturing process analysis within a unified digital environment. The research demonstrates that digital twin technology enables early detection of design inconsistencies, optimization of production parameters, reduction of material waste, and improvement of product quality. The findings indicate that the integration of digital twins into garment production contributes to greater efficiency, flexibility, and sustainability in apparel manufacturing.